2022
DOI: 10.1111/cea.14224
|View full text |Cite
|
Sign up to set email alerts
|

Peptide epitopes as biomarkers of soya sensitization in rBet v 1 immunotherapy of birch‐related soya allergy

Abstract: Background: There are no diagnostic and/or prognostic markers of the treatment outcome in patients receiving allergen immunotherapy (AIT). Although numerous allergen epitopes are known, their value in this context has not been investigated. This paper deals with re-evaluation of sera from patients who underwent AIT against rBet v 1 for treatment of their soya allergy (BASALIT trial).Objective: To evaluate the diagnostic and/or prognostic potential of allergen epitopes recognition by antibodies from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
4
0
3
Order By: Relevance
“…24 Inwieweit eine Epitopkartierung (epitope mapping) diesbezüglich hilfreich sein kann, bedarf ebenfalls noch weiterer Untersuchungen. 16 Neue Therapieformen richten sich entweder gegen das Allergen selbst, greifen in den Signalweg der allergischen Entzündung ein oder zielen auf die Modulation der IgE-Produktion ab.…”
Section: Absehbare Perspektivenunclassified
“…24 Inwieweit eine Epitopkartierung (epitope mapping) diesbezüglich hilfreich sein kann, bedarf ebenfalls noch weiterer Untersuchungen. 16 Neue Therapieformen richten sich entweder gegen das Allergen selbst, greifen in den Signalweg der allergischen Entzündung ein oder zielen auf die Modulation der IgE-Produktion ab.…”
Section: Absehbare Perspektivenunclassified
“…24 The extent to which epitope mapping can be helpful here also requires further investigation. 16 New therapies are either directed against the allergen itself, interfere with the pathway of allergic inflammation, or target the modulation of IgE production.…”
Section: Foreseeable Prospectsmentioning
confidence: 99%
“…An allergen immunotherapy against pollen allergens appears to have beneficial effects on pollen‐associated food allergy in selected patients 15 . Unfortunately, there are not yet any biomarkers that can predict efficacy 16 …”
Section: Current Research and Clinical Updatementioning
confidence: 99%
See 1 more Smart Citation
“…Another CM-OIT study developed predictive models based on epitope-specific antibody binding and showed that having lower diversity and lower binding of IgE at baseline to specific epitopes can predict SU [ 170 ]. Lastly, a study investigating the efficacy of subcutaneous injection of birch pollen allergen Bet v 1 in soya allergy reported the potential of IgE- and IgG-binding to epitopes as a biomarker for successful AIT [ 171 ].…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 99%